Prototype of Internet of Things-Based Control System Using Telegram with Bot API Method - Ferdin Permana Putra; Sahril Sabirin; Hari Soetanto (Jurnal Syntax Transformation, 2025)
This research aims to develop and implement an Internet of Things (IoT)-based device control system using Telegram with the Bot API method. This system is designed so that users can control electronic devices, such as lights and fans, remotely and in real-time through the Telegram application. The method used in this research is experimental, testing the reliability and performance of the system under various network conditions. The NodeMCU ESP8266 is used as the main microcontroller that connects the device with the internet network, while the Relay Module is used to control electrical devices. The test results show that the system works well on a sTable Wi-Fi connection, with an average response time of 2-3 seconds and a 100% success rate. However, on weak Wi-Fi connections and cellular data, there was a drop in performance with longer response times and a slight decrease in success rate. The main advantage of this system is its ease of use, which only requires the Telegram messaging app to be accessed from anywhere. Nonetheless, the system has drawbacks, such as dependence on a sTable internet connection and a limited number of devices that can be controlled. This research successfully developed an efficient and practical IoT-based device control system. The system provides a solution for better management of electronic devices, with the potential to be further developed to improve device performance and compatibility.